EPR, optical absorption and luminescence studies of Cr3+-doped antimony phosphate glasses - De Vicente, F. S. [UNESP]; Santos, F. A.; Simoes, B. S.; Dias, S. T.; Siu Li, M. (Elsevier B.V., 2014)
Antimony phosphate glasses (SbPO) doped with 3 and 6 mol% of Cr3+ were studied by Electron Paramagnetic Resonance (EPR), UV-VIS optical absorption and luminescence spectroscopy. The EPR spectra of Cr3+-doped glasses showed two principal resonance signals with effective g values at g = 5.11 and g = 1,97. UV-VIS optical absorption spectra of SbPO:Cr3+ Presented four characteristics bands at 457, 641, 675, and 705 nm related to the transitions from (4)A(2)(F) to T-4(1)(F), T-4(2)(F), T-2(1)(G), and E-2(G), respectively, of Cr3+ ions in octahedral symmetry. Optical absorption spectra of SbPO:Cr3+ allowed evaluating the crystalline field Dq, Racah parameters (B and C) and Dq/B. The calculated value of Dq/B = 2.48 indicates that Cr3+ ions in SbPO glasses are in strong ligand field sites. The optical band gap for SbPO and SbPO:Cr3+ were evaluated from the UV optical absorption edges. Luminescence measurements of pure and Cr3+-doped glasses excited with 350 nm revealed weak emission bands from 400 to 600 nm due to the P-3(1) -> S-1(0) electronic transition from Sb3+ ions. Cr(3+-)doped glasses excited with 415 nm presented Cr3+ characteristic luminescence spectra composed by two broad bands, one band centered at 645 nm (E-2 -> (4)A(2)) and another intense band from 700 to 850 nm (T-4(2) -> (4)A(2)). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Antimony phosphate glasses; Trivalent chromium; High strength crystalline field; EPR; Optical absorption; Luminescence